ANALISIS PROSES PERENCANAAN PENGANGGARAN HIBAH DAN BANTUAN SOSIAL YANG BERSUMBER DARI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (Studi Pada Dinas Pendapatan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Morowali) - Arifin, Arifin (Katalogis, 2017)
The study aims to determine and describe the process of grant-budgeting and social assistance planning based on the local Revenue and Expenditure Budgets of Morowali Districts. It also means to explore and analyze "policy" in grant-budgeting and social assistance planning in the year of 2011-2015. Tipe of study is qualitative; data collecting method include observation, documents and in-depth interviews to selected informants that are considered to have better understand and directly participated in the processof grant-budgeting and social assistance planig. Study results show that the cause of irregularities in budgetplanningis the lack of understanding from the executive and legislative in the planning process of both budgets and is elitist. In addition, the interactions or "indications" that occur tend to be collaborative because each has its own interests in the form of cooperation and accommodation for self-image of political elites and the interests of the group, rather than representing the public interest. Most of the grants and social assistance expenditures are used for organizational operations and the construction of worship houses with a nominal range of hundredsmillions to billions of rupiah. The mode of deviation or "indications" that have occurred so far in the form of placing the targeted or occupying keyÂ  positions in the nepotism beneficiary and the lack of oversight of the legislature.